A case of lockjaw in the emergency department - Giulia Marullo; Giulia Maria Bottani; Rossella Guerrieri; Adriano Basile; Paolo Aseni; Andrea Bellone (Emergency Care Journal, 2018)
Tetanus with cephalic involvement is not a typical presentation of the disease; characteristic signs and symptoms are strictly localized in cranial district, although it could frequently progress to the classical generalized form. Tetanus is still spread worldwide, especially in particular subgroups as elderly and newborn babies and in countries with an inadequate vaccine coverage.We report a case of an adult man with generalized tetanus with cephalic presentation in Emergency Department. We aim to outline how difficult it was to diagnose in an adult patient without apparent exposition of previous minimal trauma or injury because of a lot of confusing factors and slow progressing clinical signs. Prompt recognition of signs and symptoms, opportune target therapy and supportive care, in association with correct vaccination schedule, are paramount to determine the prognosis for affected patients.